Mystic sweet communion - Kirkpatrick, Jane, 1946- (Multnomah Publishers, 1998)
In 1900, Ivy Cromartie Stranahan gives up a promising teaching career to join her husband at the romote New River trading post in south Florida-but she doesn't give up her love for learning or her passion for righting wrongs. In this remarkable story of God's faithfulness and one woman's commitment, Ivy becomes a friend to the Seminole people, their teacher of forbidden English and the Christian faith, and finally, their spokesperson in their time of turmoil.